USE AND EFFECT OF COLORS IN THEATRICAL PERFORMANCE OF INDIAN CLASSICAL DANCES: भारतीय शास्त्रीय नृत्यों की रंगमंचीय प्रस्तुति में रंगों का प्रयोग एवं प्रभाव - Grover, Bhavna (International Journal of Research -GRANTHAALAYAH, 2014)
If seen in word form, the color is very small, but if it is thought, then it is contained in everything in the world. If there is no color then our life style does not exist. If there is color, then human life exists. It is believed that all colors are originally made from white color and the number of colors is calculated. Which is an important part of our daily routine. ’Rang’ which gives an idea of ​​the personality of any person. Sometimes the image of a person gets imprinted on our brain due to color. Similarly, the theater of our Indian classical dances, in which colors have been used very beautifully. Whether it is the color of the dancer’s costumes at the theater or the adjustment of colors by lighting, the colors together complete a performance. Therefore, color has a special significance in theater performances. रंग’ अगर शब्द रूप में देखा जाये तो बहुत छोटा है परन्तु यदि इसे सोचा जाए तो दुनिया की प्रत्येक वस्तु में निहित है। अगर रंग नही है तो हमारी जीवनचर्या का अस्तित्व ही नही है। रंग है तो मानव जीवन का अस्तित्व है। माना जाता है कि सभी रंग मूल रूप से श्वेत रंग से ही बने है और रंगों की संख्या अंगणित है। जो हमारी दैनिक दिनचर्या का महत्वपूर्ण हिस्सा है।‘रंग’ जिससे किसी भी व्यक्ति के व्यक्तित्व का आभास होता है। कभी-कभी तो व्यक्ति की छवि ही हमारे मस्तिष्क पर रंग के कारण अंकित हो जाती है। इसी प्रकार हमारे भारतीय शास्त्रीय नृत्यों की रंगमंचीय प्रस्तुति जिनमें रंगो का प्रयोग बहुत ही खूबसूरती से किया जाता रहा है। रंगमंच पर चाहे वह नर्तक की वेशभूषा के रंग हो अथवा प्रकाश व्यवस्था द्वारा रंगों का समायोजन, रंग ही मिलकर एक प्रस्तुति को पूर्ण करते हैं। अतः रंगमंच प्रस्तुति में रंग अपना एक विशेष महत्व रखते है।